The effects of COVID-19 on Canadian surgical residents’ education and wellness - Alam, Peter; Salimi, Ali; El Hawary, Hassan; Sioufi, Krystelle; Papanastasiou, Constantine; Thibaudeau, Stephanie (Canadian Medical Education Journal, 2022)
Background: The COVID-19 pandemic has challenged health care systems. We sought to comprehend the impact of the COVID-19 pandemic on surgical residents’ education and mental well-being across Canada. Methods: An online 51-question survey was distributed to surgical residents across all 17 Canadian post- graduate surgical residency programs. The questionnaire contained questions concerning demographic factors, perceived effects of COVID-19 pandemic on surgical training and residents’ mental health (categorically demonstrating whether it improved, stayed the same, or worsened). Health habits were measured as continuous variables and compared before and during the pandemic. Additionally, participants reported the performance of wellness offices’ response to their needs during this crisis. Results: A total of 122 out of 650 (19%) residents from all surgical specialities anonymously completed the survey. The majority (68%) reported a worsening in their surgical training. 94% of participants favored online teaching as a complementary method to in-person teaching. As to health habits, 38% reported a rise in their alcohol consumption and time spent seated. Only a minority (25%) felt happier and 41% reported experiencing more anxiety in comparison to surgical training pre-COVID-19. Merely 14% reported benefitting from wellness programs. Conclusion: The COVID-19 pandemic had a negative effect on the perceived quality of surgical training, education, and resident mental health. There is an urgent need to reconsider the implemented measures in medical education and urge us to develop better agendas to face the current or future waves.